Influence of HPV16 E2 and its localisation on the expression of matrix metalloproteinase-9 - Mühlen, Sabrina; Behren, Andreas; Iftner, Thomas; Simon, Christian (International journal of oncology, 2010)
Infection with the high-risk HPV types 16 and 18 is the major cause of cervical cancer and plays a role in the development of certain head and neck and skin cancers. We have previously demonstrated that the Early Protein 2 of the Cottontail Rabbit papillomavirus (CRPV), required for skin carcinogenesis in a rabbit model, is able to induce the expression of a matrix metalloproteinase (MMP-9); a protease known to play a key role in invasion and metastasis. However, as of now we do not understand the underlying mechanism of activation nor relevance for the human system. Here, we report that high-risk human papillomavirus HPV16 E2 similar to our previously reported results on CRPV E2 activates the human MMP-9 promoter predominantly via the MEK1-ERK1/2-AP-1-signaling pathway. In addition this activation is associated with a nuclear sub-localisation of HPV16-E2 suggesting a nuclear protein-protein or protein-DNA interaction of E2 as the underlying mechanism of activation.
Gesehen am 10.05.2023